Influence of Cleats-Surface Interaction on the Performance and Risk of Injury in Soccer: A Systematic Review - Diogo C. F. Silva; Rubim Santos; João Paulo Vilas-Boas; Rui Macedo; António Mesquita Montes; Andreia S. P. Sousa (Applied Bionics and Biomechanics)
Objective. To review the influence of cleats-surface interaction on the performance and risk of injury in soccer athletes. Design. Systematic review. Data Sources. Scopus, Web of science, PubMed, and B-on. Eligibility Criteria. Full experimental and original papers, written in English that studied the influence of soccer cleats on sports performance and injury risk in artificial or natural grass. Results. Twenty-three articles were included in this review: nine related to performance and fourteen to injury risk. On artificial grass, the soft ground model on dry and wet conditions and the turf model in wet conditions are related to worse performance. Compared to rounded studs, bladed ones improve performance during changes of directions in both natural and synthetic grass. Cleat models presenting better traction on the stance leg improve ball velocity while those presenting a homogeneous pressure across the foot promote better kicking accuracy. Bladed studs can be considered less secure by increasing plantar pressure on lateral border. The turf model decrease peak plantar pressure compared to other studded models. Conclusion. The soft ground model provides lower performance especially on artificial grass, while the turf model provides a high protective effect in both fields.